Use of augmented reality software as a pedagogical tool: Virtuali Tee app presentation - Quinquiolo, Natália Carvalho Rosas (2020)
The use of technologies in education is becoming increasingly frequent and important in the modern society. In this context, the present work seeks to present to students of the eighth year of elementary school, aged between 14 and 15 years, the possibilities of applying augmented reality software that allows students to visualize and interact with some systems of the human body, thus favoring the learning process. To do so, students downloaded a software in their smartphones, the Virtuali tee, that works in conjunction with a specific tee that allows the user to virtually contact the human body and some of its organs and systems in an interactive and dynamic way.